Diseño de un estudio de prefactibilidad para la implementación del servicio de catering en la empresa Proveservices S.A – Portoviejo - Cedeño Loor, María Magdalena (2014)
The objective of this research was to perform a feasibility study for the implementation of the Catering Service in the city of Portoviejo at PROVESERVICES S.A, which applied as first technical interview to get a clearer view on the services provided by the company and thus be able to apply the survey to obtain relevant information on the needs and preferences of consumers. Indeed a market study was conducted to understand the behavior of the consumer, competition and apply the strategies needed to define current and potential demand by applying descriptive research, the method of deductive, analytic and synthetic in each of the phases was applied in this study. With reference, it was determined by the technical study the location of the premises, the decision for the management of human and material resources through diagrams according to the covenant which is made. Giving continuity applied a financial study that profitability could meet and as a result was positive, therefore the project was cost effective. The business decision is necessary the feasibility study by the guarantee of the numerical information, for this reason was socialized the proposal to the owner of the company as a contribution to determine more accurately reliable assessment of financial profitability indicators.